1994
DOI: 10.1063/1.112280
|View full text |Cite
|
Sign up to set email alerts
|

Growth of KNbO3 thin films on MgO by pulsed laser deposition

Abstract: Crystalline and stoichiometric KNbO3 thin films have been grown on (100) oriented MgO substrates by pulsed laser deposition technique. Electron microprobe analysis and Rutherford backscattering spectroscopy of the films show a progressive loss of K with increasing substrate-target distance. To compensate for this K loss the ceramic KNbO3 targets were enriched with K2CO3 powder, pressed at room temperature, and sintered at 650 °C. For a substrate-target distance of 6 cm, targets with [K]/[Nb] molar ratio=2.85 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…KNbO 3 is one of the most important ferroelectric perovskite oxides. Since the discovery of ferroelectric nature in 1951 [14], KNbO 3 has shown potential for piezoelectric and ferroelectric applications due to its large electromechanical coupling factor, high Curie temperature, the promising nonlinear optical property, and lead-free and environmentally friendly nature [15][16][17]. Taking into account this high technological importance, it is surprising that there are few experimental and theoretical studies reported dealing with KNbO 3 (0 0 1) surfaces.…”
Section: Introductionmentioning
confidence: 94%
“…KNbO 3 is one of the most important ferroelectric perovskite oxides. Since the discovery of ferroelectric nature in 1951 [14], KNbO 3 has shown potential for piezoelectric and ferroelectric applications due to its large electromechanical coupling factor, high Curie temperature, the promising nonlinear optical property, and lead-free and environmentally friendly nature [15][16][17]. Taking into account this high technological importance, it is surprising that there are few experimental and theoretical studies reported dealing with KNbO 3 (0 0 1) surfaces.…”
Section: Introductionmentioning
confidence: 94%
“…expected to promote the development of cation vacancies in the deposited film. 9,10 Under these circumstances, by keeping all the other parameters constant, increasing the sputtering power density would increase the growth rate which would, in turn, reduce the number of cation vacancies. This allows for control on the final number of cation vacancies in the films.…”
Section: Aging Of Magnetic Properties In Mgo Filmsmentioning
confidence: 99%
“…The simpler KNbO 3 crystal has shown good performance in nonlinear optical applications and it has recently also been studied in thin film form. [18][19][20] The addition of Na provides the opportunity to adjust the lattice parameter of the growing film since the lattice parameters of (Na x ,K 1Ϫx )NbO 3 are smaller than those of KNbO 3 . 12 Na addition can also modify the dielectric and piezoelectric properties of KNbO 3 .…”
mentioning
confidence: 99%